Factors Affecting Teachers’ Stage of Concern on Evaluation System of Primary School Curriculum Innovation - Badeni Badeni (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of the study is to describe the teachers’ stage of concern for the evaluation of primary school innovation and factors affecting teachers’ stage of concern. The approach used in this study was a descriptive study. Data related to factors affecting teachers' stage of concern to the evaluation of primary school curriculum innovation were collected in the form of forum discussion and study of related literature. While data on teacher's stage of concern itself to the evaluation system of primary school curriculum innovation were collected, classified, processed and analyzed by using the norms of the group in the calculation of percentile. The findings of this study were 10 % in a stage of awareness, 14 % in the stage of information; 2 % in the stage of personnel;12 % in the stage of management; 20 % in the stage of consequence;12 % in the stage of collaboration and 20 % in the stage of refocusing. Teachers’ stage of concern to the evaluation of primary school curriculum innovation was low. It was caused by (a) the lack of understanding of primary school teachers on information received, (b) lack of examples and evidence of the benefits of accepted curriculum innovation in school practices, (c) lack of training by trainers in applying new curriculum, (d) so complex in evaluating and (e) the curriculum is continually changing. (f) teacher involvement in implementing program and the training needs (g) adequate time to learn, practice, master and apply what needs to be learned about an curriculum innovation (h) teachers’ commitment to implement the curriculum innovation; (i); principal knowledge of educational change; (j) principals role in carrying out programs; (k) principals' moral support and active participation; (l) collaborative planning by teachers and administrators.